Image-D4.5: Tracers For Supercritical Conditions - Muller, Jiri (Zenodo, 2016)
This document describes “Tracers for supercritical conditions”. It consists of 2 parts. The first part deals with behaviour of Perfluorinated cyclic hydrocarbons (PFCs) tracers tested at supercritical conditions obtained from static and dynamic experiments performed at IFE. The second part consists of two reports describing field tests tracers studies at Krafla field performed in the summer 2016 by BRGM, CNR, ISOR and LV. : FP7